Transformation of Strawberry Farmers into Agrotourism Operators in Batu City: A Case Study of Lumbung Stroberi Pandanrejo - Rum Van Royensyah; Muhammad Hasyim; Noor Azizah (CV Projurnal Mitra Publikasi, 2025)
The transformation of strawberry farmers into agrotourism operators represents a paradigm shift in rural development from pure agriculture to service-based tourism economy. This study analyzes the transformation process of strawberry farmers in Pandanrejo Village, Batu City, East Java, using a qualitative case study approach. Data were collected through in-depth interviews with 18 informants, participatory observation, and document analysis. Results indicate that transformation occurred in three stages: (1) crisis of traditional agriculture due to price fluctuations, (2) BUMDes-based agrotourism initiation in 2018-2019, and (3) institutionalization of sustainable tourism. Key driving factors include economic incentives (40-60% income increase), policy support from Batu City Tourism Office, and social capital of mutual cooperation (Sinoman Batu Association). However, challenges include infrastructure limitations, conflicts with traditional middlemen, and risks of cultural commodification. This study recommends strengthening BUMDes managerial capacity and developing agrotourism zoning regulations to maintain balance between commercialization and sustainability.